FUNGSI MANAJEMEN DAKWAH DALAM PENDIDIKAN DAKWAH TRANSFORMATIF DI PESANTREN ISTIQOMAH AL-AMIN KECAMATAN CANDIPURO LAMPUNG SELATAN - Suslina; Rouf Tamim (International Journal of Publication Unit (IUJP) Agus Salim Metro, 2020)
This study aims to determine how the function of Da'wah Management in Transformative Da'wah Education at the Istiqomah Al-Amin Islamic Boarding School, Candipuro District, South Lampung. The research approach used is a qualitative approach. While this type of research is field research. Sources of research data are Islamic boarding school caregivers, cottage teachers (Ustadz and Ustadzah). Methods of data collection is done by observation, interviews and documentation. The data processing method in this study was obtained through research instruments in four stages, namely: data reduction, data presentation, data verification and triangulation.